GROUP GUIDANCE WITH SCENARIO MATRIX ANALYSIS (SMAL) SELF-EFFICACY IN NON-FAVORITE JUNIOR HIGH SCHOOL STUDENTS - Aliyah, Urotul; Adinda, Lia Nur (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to test the effectiveness of Scenario Matrix Analysis for Learning (SMAL) on students of a non-favorite junior high school in North Kalimantan. Self-efficacy is an individual's belief in their ability to complete tasks and face challenges. Through a systematic group guidance approach, students are trained to identify problems, analyze causal factors, formulate solutions, and reflect on the results in a structured manner. The research method used was a pre-experiment with a one-group pretest-posttest design. The results showed a significant increase in self-efficacy scores after participating in the intervention. These findings indicate that Group Guidance with SMAL is effective in improving the self-efficacy of non-favorite junior high school students.